Gender-Based Patterns of Public Space Utilization: A Systematic Literature Review - Hidhayad, Aulia; Kusdiwanggo, Susilo; Dwi Wulandari, Lisa (Graduate School Universitas Brawijaya, 2026)
Objective: This study aims to identify and analyze gender-based patterns in the use, perception, and experience of public spaces through a Systematic Literature Review (SLR) approach. Design/Methods/Approach: The research collected and reviewed 33 scientific articles published between 2015 and 2026 from the Scopus and ScienceDirect databases using specific keywords related to gender behavior and public space. Findings: The findings reveal that men and women interact with public spaces differently due to physical, social, and psychological factors. Men tend to use public areas for physical and recreational activities, while women are more influenced by safety, accessibility, and social interaction. Environmental aspects such as lighting, walkability, and spatial design strongly affect users’ sense of comfort and security. Moreover, cultural and social norms play a significant role in shaping gendered behaviors and perceptions within urban spaces. Originality/Value: This research expands both theoretical and practical understanding of patterns in the use of public spaces based on gender. Practical/Policy implication: Furthermore, the findings provide a foundation for urban designers to adopt a gender-responsive spatial planning approach, particularly in the design of public spaces. Keywords: Gender-based patterns; public spaces; perception; inclusivity; systematic literature review